2007
DOI: 10.1002/app.25479
|View full text |Cite
|
Sign up to set email alerts
|

Novel heat‐conductive composite silicone rubber

Abstract: The silicone rubber with good thermal conductivity and electrical insulation was obtained by taking vinyl endblocked polymethylsiloxane as basic gum and thermally conductive, but electrically insulating hybrid Al 2 O 3 powder as fillers. The effects of the amount of Al 2 O 3 on the thermal conductivity, coefficient of thermal expansion (CTE), heat stability, and mechanical properties of the silicone rubber were investigated, and it was found that the thermal conductivity and heat stability increased, but the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 20 publications
(16 reference statements)
2
68
0
1
Order By: Relevance
“…The incorporation of filler particles enhanced the stiffness but reduces the flexibility due to poorer mobility of molecular chains [17]. Zhou et al [18] reported that higher filler loading (40 vol%) in silicone rubber, leads to difficulty in processing and the mechanical property is degraded. The flexural strength decreased with increasing amount of filler loadings.…”
Section: Methodsmentioning
confidence: 98%
“…The incorporation of filler particles enhanced the stiffness but reduces the flexibility due to poorer mobility of molecular chains [17]. Zhou et al [18] reported that higher filler loading (40 vol%) in silicone rubber, leads to difficulty in processing and the mechanical property is degraded. The flexural strength decreased with increasing amount of filler loadings.…”
Section: Methodsmentioning
confidence: 98%
“…And the third way is to transfer the generated heat from inside to outside. Much research works on thermal conductivity of rubber composites have been done [1][2][3][4][5][6][7][8], however, there are rather few reports dealing with the applications in tires [9][10][11]. Wang et al [9] indicated that nano-zinc oxide could not only reinforce ethylene propylene diene monomer (EPDM) but also improve thermal conductivity significantly, and the composites could serve in dynamic conditions with longer expected service life.…”
Section: Introductionmentioning
confidence: 99%
“…0.10-0.25 W/m -1 ·K -1 ), and it has been widely recognized that the thermal conductivity of these polymers has to be enhanced to lower the energy loss and increase the stability of the devices. With the increasing demand for high density power and energy transmission of electronic devices, fabrication of insulating polymer materials with high thermal conductivity has become crucial [1][2][3][4]. High crystallization and orientation of polymer can greatly enhance the thermal conductivity along the orientation direction, but they usually have difficulties of processing [5].…”
Section: Introductionmentioning
confidence: 99%